Benthic meiofauna as indicator of ecological changes in estuarine ecosystems: The use of nematodes in ecological quality assessment - Alves, Ana (2013)
a b s t r a c t Estuarine meiofauna communities have been only recently considered to be good indicators of ecological quality, exhibiting several advantages over macrofauna, such as their small size, high abundance, rapid generation times and absence of a planktonic phase. In estuaries we must account not only for a great natural variability along the estuarine gradient (e.g. sediment type and dynamics, oxygen availability, temperature and flow speed) but also for the existence of anthropogenic pressures (e.g. high local population density, presence of harbors and dredging activities). Spatial and temporal biodiversity patterns of meiofauna and freeliving marine nematodes were studied in the Mondego estuary (Portugal). Both taxonomic and functional approaches were applied to nematode communities in order to describe the community structure and to relate it with the environmental parameters along the estuary. At all sampling events, nematode assemblages reflected the estuarine gradient, and salinity and grain size composition were confirmed to be the main abiotic factors controlling the distribution of the assemblages. Moreover, the low temporal variability may indicate that natural variability is superimposed by the anthropogenic pressures present in some areas of the estuary. The characterization of both meiofauna and nematode assemblages highlighted the usefulness of the integration of both taxonomic and functional attributes, which must be taken into consideration when assessing the ecological status of estuaries.